The Effects of Fraud and Lawsuit Revelation on U.S. Executive Turnover and Compensation - Persons, Obeua S. (Journal of business ethics, 2006)
This study investigates the impact of fraud/lawsuit revelation on U.S. top executive turnover and compensation. It also examines potential explanatory variables affecting the executive turnover and compensation among U.S. fraud/lawsuit firms. Four important findings are documented. First, there was significantly higher executive turnover among U.S. firms with fraud/lawsuit revelation in the Wall Street Journal than matched firms without such revelation. Second, although on average, U.S. top executives received an increase in cash compensation after fraud/lawsuit revelation, this increase is smaller than that of matched non-fraud/lawsuit firms. Third, fraud/lawsuit firms were more likely to change top executive when chief executive officer (CEO) was not the board chairman and CEO had been on the board for a short time. Fourth, fraud/lawsuit firms were more likely to reduce their executive cash compensation when profitability was low, firms were involved in fraud, the compensation committee size was small, and the board met more often. These findings indicate that although, in general, U.S. fraud/lawsuits firms did not reduce their executive cash compensation, those involved in fraud were more likely to reduce their executive cash compensation than to change their top executives. The finding, that ethical standards is not a significant factor for U.S. executive turnover nor compensation reduction, suggests that ethics appears to play no part in the board’s decisions, and that U.S. firms may have ethical standards in writing but they do not implement nor enforce the standards.